'My young Tasmanian cousin': animal lives and companions on board and beyond the Flying Squadron, 1869–1873. (2nd July 2020) - McCreery, Cindy
ABSTRACT: Recent scholarship has drawn attention to the complexity of animal–human relationships on board ships, but we still know relatively little about crewmembers' responses to animals on board nineteenth-century British warships, especially on overseas voyages. The 1869–70 Flying Squadron voyage provides a useful case study. On board each of the squadron's six warships sailed dozens of officers, hundreds of sailors and a fluctuating number of live animals. This article focuses on the Flying Squadron diary of Midshipman Marcus McCausland, plus accounts and memoirs by fellow crewmembers, which discuss animals' shipboard role, but also reflect on naval personnel's relations with one another as well as civilians. The last section of the article considers McCausland's service and death while serving in anti-slavery patrols off East Africa as recorded in memoirs and official correspondence. These sources reveal McCausland as a complex, ambivalent figure, whose relationship with animals, women, naval authority, and, later, slavers and the enslaved in East Africa, speaks to larger tensions over masculine and naval authority, and naval memory, in the nineteenth-century global maritime world. As well, the sources reveal the continuing importance of human companionship and memorialisation in sustaining shipboard communities.